Utilization of Powerful Words in Compiling Effective Communication Materials - Zainudin Zainudin; Asef Wildan Munfadlila; Saptono Hadi (Journal of Development Research, 2021)
In the Indonesian language course, communication can be included in the area of speaking and writing. To carry out effective communication, the stages must be carried out, namely fact finding, planning, communicating, and evaluation. The purpose of this research is to describe the concept map of effective communication material based on powerful words. This research method uses qualitative research methods with data sources in the form of books by Erwin Parengkuan et al. entitled Talk-inc Points published by Gramedia Pustaka Utama, Trianto's book entitled Designing an innovative-progressive learning model published by KencanaPrenada Media Group. The data analysis carried out by researchers is as follows: (1) data reduction (2) displaying data by compiling relevant data, (3) drawing conclusions to get a meaning that scattered symptoms have deep meaning. The results of this study indicate that the use of powerful words in the preparation of effective communication materials produces a concept map for effective communication materials. Making a concept map for effective communication material becomes easier to learn and understand, that in effective communication there are four stages that must be done, namely fact finding, planning, communicating, and evaluation.